p-Type Transparent NiO Thin Films By e-Beam Evaporation Techniques - K.J. Patel1,; M.S. Desai1,; C.J. Panchal1,; Bharati Rehani2 (Журнал нано- та електронної фізики)
Nickel oxide (NiO) semiconductors thin films were prepared by e-beam evaporation technique at different substrate temperatures ranging from room temperature to 400 °C on glass substrate. Glancing incident X-ray diffraction depict that with the increases in substrate temperature the preferred orientation changes from (111) to (200) direction. Atomic force microscopy was used to investigate the surface morphology of the NiO thin films. The transmittance of NiO thin film increases with substrate temperature. NiO thin film was also deposited on n-type indium tin oxide (ITO) thin films to investigate the diode characteristic of p-NiO/n-ITO junction.